Association of anaplastic lymphoma kinase variants and alterations with ensartinib response duration in non‐small cell lung cancer. Issue 17 (20th July 2021) - Hou, Donghui; Zheng, Xiaomin; Song, Wei; Liu, Xiaoqing; Wang, Sicong; Zhou, Lina; Tao, Xiuli; Lv, Lv; Sun, Qi; Jin, Yujing; Zhang, Zewei; Ding, Lieming; et al.
Abstract: Background: Here, we aimed to assess the association of ALK variants and alterations with ensartinib response duration in NSCLC, and explore the potential value of computed tomography (CT) radiomic features in predicting progression‐free survival (PFS). Methods: We enrolled 88 patients with identified ALK variant NSCLC in a multicenter phase 2 trial, and assessed the impact of ALK variants and secondary ALK alterations on the clinical outcome (response duration) of patients receiving ensartinib. We also established a multifactorial model of clinicopathological and quantitative CT radiomic features to predict PFS and risk stratification. Kaplan–Meier analysis was conducted to identify risk factors for tumor progression. Results: Univariate analysis indicated a statistical difference ( p = 0.035) in PFS among ALK variants in three classifications (V1, V3, and other variants). Secondary ALK alterations were adversely associated with PFS both in univariate ( p = 0.008) and multivariate ( p = 0.04) analyses and could identify patients at high risk for early progression in the Kaplan–Meier analysis ( p = 0.002). Additionally, response duration to crizotinib <1 year and liver metastasis were adversely associated with PFS. The combined model, composed of clinicopathological signature and CT radiomic signature, showed good prediction ability with the area under the receiver operating characteristic curve being 0.85, and 0.89 in the training and validation dataset respectively. Conclusions: Our study showed that secondary ALK alterations were adversely associated with ensartinib efficacy, and that ALK variants might not correlate with PFS. The quantitative radiomic signature provided added prognostic prediction value to the clinicopathological features. Abstract : The secondary ALK alterations were adversely associated with ensartinib response duration in NSCLC, and ALK variants might not correlate with PFS. CT quantitative radiomic signature could add prognostic prediction value of clinicopathological features.